Accelerated flowering time reduces lifetime water use without penalizing reproductive performance in Arabidopsis. (12th March 2019) - Ferguson, John N.; Meyer, Rhonda C.; Edwards, Kieron D.; Humphry, Matt; Brendel, Oliver; Bechtold, Ulrike
Abstract: Natural selection driven by water availability has resulted in considerable variation for traits associated with drought tolerance and leaf‐level water‐use efficiency ( WUE ). In Arabidopsis, little is known about the variation of whole‐plant water use (PWU) and whole‐plant WUE ( transpiration efficiency ). To investigate the genetic basis of PWU, we developed a novel proxy trait by combining flowering time and rosette water use to estimate lifetime PWU. We validated its usefulness for large‐scale screening of mapping populations in a subset of ecotypes. This parameter subsequently facilitated the screening of water use and drought tolerance traits in a recombinant inbred line population derived from two Arabidopsis accessions with distinct water‐use strategies, namely, C24 (low PWU) and Col‐0 (high PWU). Subsequent quantitative trait loci mapping and validation through near‐isogenic lines identified two causal quantitative trait loci, which showed that a combination of weak and nonfunctional alleles of the FRIGIDA (FRI) and FLOWERING LOCUS C (FLC) genes substantially reduced plant water use due to their control of flowering time. Crucially, we observed that reducing flowering time and consequently water use did not penalize reproductive performance, as such water productivity (seed produced per unit of water transpired) improved. Natural polymorphisms of FRI and FLC have previously been elucidated as key determinants of natural variation in intrinsic WUE (δ 13 C). However, in the genetic backgrounds tested here, drought tolerance traits, stomatal conductance, δ 13 C. and rosette water use were independent of allelic variation at FRI and FLC, suggesting that flowering is critical in determining lifetime PWU but not always leaf‐level traits. Abstract : Accelerated flowering time achieved through nonfunctional and weak alleles of flowering time genes FRIGIDA ( FRI ) and FLOWERING LOCUS C ( FLC ) reduce water use in Arabidopsis thaliana without detrimentally impacting reproductive output.